2012
DOI: 10.1159/000339944
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin for Neuropathic Pain: Linking Traditional Medicine and Molecular Biology

Abstract: Capsaicin has long been used as a traditional medicine to treat pain and, recently, its mechanism of analgesic action has been discovered. This review article documents the clinical development of capsaicin to demonstrate that pharmacognosy still has a profound influence on modern-day drug development programs. Capsaicin is a highly selective agonist for the transient receptor potential channel vanilloid-receptor type 1 (TRPV1), which is expressed on central and peripheral terminals of nociceptive primary sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 129 publications
1
29
0
3
Order By: Relevance
“…At single symptom level a weak association was found between burning and pressure-evoked pain at baseline and response. Since the burning quality is frequently associated with the presence of TRPV1 receptors on nociceptors this association is in line with the proposed mechanism of action of capsaicin 21 .…”
Section: Treatment Responders Based On the Paindetect Baseline Valuessupporting
confidence: 79%
“…At single symptom level a weak association was found between burning and pressure-evoked pain at baseline and response. Since the burning quality is frequently associated with the presence of TRPV1 receptors on nociceptors this association is in line with the proposed mechanism of action of capsaicin 21 .…”
Section: Treatment Responders Based On the Paindetect Baseline Valuessupporting
confidence: 79%
“…Capsaicin (8-methyl-N-vanillyl-6-nonenamide), a lipophilic alkaloid found in hot red chili peppers of the genus Capsicum (hot chili peppers), has long been used to treat persistent pain, such as osteoarthritic pain, postherpetic neuralgia of the trigeminal nerve, cluster headache, diabetic neuropathy, HIV-associated distal sensory neuropathy, and intractable pain in cancer patients [1,2,3,4,5,6,7,8,9,10,11,12]. Capsaicin is an agonist of transient receptor potential cation channel, subfamily V, member 1 (TRPV1), which provides the sensation of pain (nociception).…”
Section: Introductionmentioning
confidence: 99%
“…It is activated by chemical and physical stimuli, such as heat, low pH, capsaicin, and certain inflammatory mediators [57]. Prolonged activation of TRPV1 by capsaicin is discussed to cause desensitization and, thus, reduced pain sensation [58]. Beyond pain, some few studies also found an anti-inflammatory potential of capsaicin: it can inhibit paw inflammation in arthritic rats [59] and ethanol-induced inflammation of the gastric mucosa in rats [60].…”
Section: Plant-derived Compounds Tested In Clinical Trialsmentioning
confidence: 99%